40th AIAA/ASME/SAE/ASEE Joint Propulsion Conference and Exhibit 2004
DOI: 10.2514/6.2004-4116
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Distributions in Hollow Cathode Emitters

Abstract: Life-limiting processes in hollow cathodes are determined largely by the temperature of the emitter. To support development of cathode life models we have developed a noncontact temperature measurement technique which employs a stepper motor-driven fiber optic probe. The probe is driven inside the hollow cathode and collects light radiated by the hot interior surface of the emitter. Ratio pyrometry is used determine the axial temperature profile. Thermocouples on the orifice plate provide measurements ofthe ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…14,15,16,23 Cathode-to-ground voltage results in Figure 8 indicate that, in general, the cathode-toground voltage became more negative as the flow rate was increased. At a flow rate of 19 sccm, configuration 1 operated in plume mode for all discharge currents.…”
Section: Resultsmentioning
confidence: 90%
“…14,15,16,23 Cathode-to-ground voltage results in Figure 8 indicate that, in general, the cathode-toground voltage became more negative as the flow rate was increased. At a flow rate of 19 sccm, configuration 1 operated in plume mode for all discharge currents.…”
Section: Resultsmentioning
confidence: 90%
“…The system was calibrated in situ using the hollow cathode heater and thermocouples on the orifice plate, which compensates for cavity and surface effects on the effective emittance. Extensive testing demonstrated that the measurements were repeatable at a given operating point to within 1-2 C. In regards to the thermocouples, under nearly isothermal conditions during calibration, the readings agreed to within 2 C. During cathode operation, however, they differed by 10-15 C. A more detailed description of the system and methods used for the measurements is provided in [19,20]. Results from an earlier test with a different insert and slightly lower flow rate are also plotted and show similar behavior.…”
Section: Resultsmentioning
confidence: 95%
“…This corresponds to an orifice plate temperature of at most 1030 °C, as shown in Figure 1. It has been shown that the emitter on a cathode can be up to 90 °C cooler 26 or 100 °C hotter 27 than the orifice plate temperature. For the purposes of this study, the lifetime results are shown over a +/-100 °C temperature span on the orifice plate temperatures.…”
Section: Insert Barium Depletionmentioning
confidence: 99%
“…25 The peak insert temperature measured on a similar cathode was 1180 °C at 12 A of emission current. 26 Using that peak temperature and an estimated depletion depth of 500 µm, the model outlined in Refs. 21 and 23 yields a lifetime estimate of 30 khrs.…”
Section: Insert Barium Depletionmentioning
confidence: 99%
See 1 more Smart Citation